2010
DOI: 10.1590/s0100-39842010000500012
|View full text |Cite
|
Sign up to set email alerts
|

Peculiaridades da radioterapia em idosos

Abstract: É sabido que o envelhecimento da população do mundo durante o século XX e no início deste novo século constitui um desafio de primeira ordem para as nações, especialmente no campo socioeconômico. Um aspecto importante do envelhecimento populacional global é que, para grupos de idade mais avançada, a prevalência das doenças degenerativas também é maior, incluindo as doenças malignas. No universo de pacientes portadores de câncer, por outro lado, metade destes receberá radioterapia em algum momento de sua doença… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…27,28 Although older age is not a contraindication for certain treatments, elderly patients with poor functional capacity present a considerable risk of toxicity, which may turn the treatment inefficient or even fatal. 29,30 The burden of drug prescription in end-of-life patients has been currently discussed, above all due to the benefit limitation that can be achieved in the survival time of these patients. In general, elderly oncological patients receive more drugs compared to younger patients.…”
Section: Interpretationsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Although older age is not a contraindication for certain treatments, elderly patients with poor functional capacity present a considerable risk of toxicity, which may turn the treatment inefficient or even fatal. 29,30 The burden of drug prescription in end-of-life patients has been currently discussed, above all due to the benefit limitation that can be achieved in the survival time of these patients. In general, elderly oncological patients receive more drugs compared to younger patients.…”
Section: Interpretationsmentioning
confidence: 99%
“…31,32 In this context, it is argued that physicians often decide to not expose aged patients to aggressive therapies, and this perhaps configures a generalized limitation to cancer care among elderly patients. 29 Northern regions in Brazil historically present a reduced availability of healthcare, including oncological services, which are more concentrated in southern regions. [33][34][35] This assertion is applied both to chemotherapy and radiotherapy services, an important factor to observe when evaluating costs according to treatment modalities, especially the radiotherapy attendance, which demands a complex infrastructure for its operation.…”
Section: Interpretationsmentioning
confidence: 99%
“…Chen et al 11 demonstrated that during radiotherapy in older adults, the irradiating area of treatment in patients already treated or undergoing treatment with nephrotoxic drugs deserves attention, as the simultaneous or sequential irradiation of one or both kidneys, even if inadvertently, may cause additional irreparable kidney damage.…”
Section: Introductionmentioning
confidence: 99%